The use of the sections of the Noble Prophetic Hadith in Islamic sects in the book Majma' Al-BahrainBy Sheikh Fakhr Al-Din Al-Turahi (1085 AH), one of the scholars of the eleventh century AH (Journal of Imam Al-Kadhim College, 2024)
Hadith is one of the most noble sciences, and its source is Allah the Almighty, the Messenger and his pure family, as its connection to them comes in second place after the words of Allah the Almighty, and its benefit is in the service of the noble Sharia, as it is linked to the rest of the other Islamic sciences, such as (the science of jurisprudence, the science of principles, and the science of men), and every jurist must know the Sunnah in order to adhere to it, and the Sunnah in it represented by the noble prophetic hadith is needed by the jurist, the hadith scholar, the researcher, and everyone who specializes in the field of Islamic sciences more than he needs the rest of the other sources of legislation such as the Holy Quran, consensus, and reason, because those sources specific to Islamic legislation are the basis for jurisprudential ijtihad and the derivation of legal rulings, as it is difficult to know all the rulings except through the pure prophetic Sunnah, and because the Holy Quran did not prove all the rulings and their legal exits, and consensus is not able to be an argument in many rulings, and reason cannot receive all the branches of rulings and their legislation, because reason is deficient in many matters, and we have nothing left but commitment.